THE LAXITY OF CRIMINAL LAW ENFORCEMENT IN INDONESIA AND EFFORTS TO OVERCOME IT - Bambang Ali Kusumo (Universitas Slamet Riyadi, 2021)
The laxity of criminal law enforcement lied in the surveillance function in criminal justice management system and civil law culture. Effort needed to be done by empowering functions of broader Supreme Court surveillance, not only surveillance that proceeding in the court but also surveillance from all criminal law enforcement process. Beside that for the sake of actualizing justice in the society, civil law culture required to be used broad interpretation and always updated legal reform.